2014
DOI: 10.1186/s12873-014-0025-y
|View full text |Cite
|
Sign up to set email alerts
|

Pain, distress, and anticipated recovery for older versus younger emergency department patients after motor vehicle collision

Abstract: BackgroundMotor vehicle collisions (MVCs) are the second most common injury mechanism resulting in emergency department (ED) visits by older adults. MVCs result in substantial pain and psychological distress among younger individuals, but little is known about the occurrence of these symptoms in older individuals. We describe the frequency of and characteristics associated with pain, distress, and anticipated time for physical and emotional recovery for older adults presenting to the ED after MVC in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…These results seem to be consistent with results reported in other studies (Yim et al., ; Pereira et al., ). Significantly higher proportions of elderly patients were triaged as being in the critical, or urgent category when compared to younger adults (Yim et al., ; Pereira et al., ), and therefore were mostly hospitalized and given therapy according to medical recommendations. In addition, elderly patients with critical conditions such as myocardial infarction or stroke are usually not in a situation to interview them.…”
Section: Discussionsupporting
confidence: 94%
“…These results seem to be consistent with results reported in other studies (Yim et al., ; Pereira et al., ). Significantly higher proportions of elderly patients were triaged as being in the critical, or urgent category when compared to younger adults (Yim et al., ; Pereira et al., ), and therefore were mostly hospitalized and given therapy according to medical recommendations. In addition, elderly patients with critical conditions such as myocardial infarction or stroke are usually not in a situation to interview them.…”
Section: Discussionsupporting
confidence: 94%
“…In a sample of N = 1,039 adults after a motor vehicle collision, Pereira et al. () found an association between peritraumatic distress and pain catastrophizing as measured by the 13‐item Pain Catastrophizing Scale.…”
Section: Resultsmentioning
confidence: 99%
“…One prospective study assessed disordered eating symptoms in N = 698 (n = 113 at follow-up) individuals after exposure to media coverage of an earthquake and found that peritraumatic distress was associated with bulimia in hierarchical regression analysis. In a sample of N = 1,039 adults after a motor vehicle collision, Pereira et al (2014) found an association between peritraumatic distress and pain catastrophizing as measured by the 13-item Pain Catastrophizing Scale.…”
Section: Peritraumatic Distress and Psychiatric Outcomes Other Than Ptsdmentioning
confidence: 94%
“…3, 35, 36 Patients were also asked to rate their pain severity overall and for 13 body parts at the time of the ED evaluation (0–10 scale). 37 Patients who had already received an analgesic were asked to recall their pain severity prior to taking the analgesic, and this was value was used to represent the patient’s ED pain. Perceived social support was measured by asking four questions from the Medical Outcomes Study Social Support Survey Instrument.…”
Section: Methodsmentioning
confidence: 99%